ANALISIS PENGARUH COMPUTER ANXIETY DAN SELF EFFICACY TERHADAP KEAHLIAN PENGGUNAAN INTERNET PADA MAHASISWA - Handayani, Rini (Sekolah Tinggi Ilmu Ekonomi Atma Bhakti, 2010)
The objectives of the research are to examine computer anxiety and self efficacy factor that influence of ability to use an internet. This study is implemented in STIE Atma Bhakti Surakarta. Data collection used is quesionnare by 128 student with convinience sampling method. The data were analyzed by using multiple regression by SPSS 13.5 software. Study results show that computer anxiety factor are significant positive influence of ability to use an internet and self efficacy is insignificant positive influence of ability to use internet.